1998
DOI: 10.1116/1.590301
|View full text |Cite
|
Sign up to set email alerts
|

What can electron paramagnetic resonance tell us about the Si/SiO2 system?

Abstract: Electron paramagnetic resonance ͑EPR͒ measurements of Si/SiO 2 systems began over 30 years ago. Most EPR studies of Si/SiO 2 systems have dealt with two families of defects: P b centers and EЈ centers. Several variants from each group have been observed in a wide range of Si/SiO 2 samples. Some of the most basic aspects of this extensive, body of work remain controversial. EPR is an extraordinary powerful analytical tool quite widely utilized in chemistry, biomedical research, and solid state physics. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
265
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(280 citation statements)
references
References 83 publications
11
265
4
Order By: Relevance
“…͑i͒ A narrow line with g ranging from 2.0004 to 2.0010 and width ͑peak-to-peak first derivative͒ ⌬H pp about 3-5 G. This line can be assigned to the well-known EЈ center, whose origin is essentially a silicon dangling bond with "SiwO 3 configuration. 25 27 We will name the defect observed in our samples as Si DB .…”
Section: Resultsmentioning
confidence: 99%
“…͑i͒ A narrow line with g ranging from 2.0004 to 2.0010 and width ͑peak-to-peak first derivative͒ ⌬H pp about 3-5 G. This line can be assigned to the well-known EЈ center, whose origin is essentially a silicon dangling bond with "SiwO 3 configuration. 25 27 We will name the defect observed in our samples as Si DB .…”
Section: Resultsmentioning
confidence: 99%
“…For the c-Si (111) surface orientation, all P b centers point into a direction perpendicular to the interface. Because of this, their microscopic anisotropy is reflected by the ESR as well as EDMR spectra as shown repeatedly in the literature [17,18]. First pEDMR studies at the P b -center have been carried out recently by Friedrich et al [18] which revealed that charge carrier trapping and recombination can take place without the presence of additional shallow trapping centers through a two step trapping/readjustment direct capture process that had been described theoretically first by Shockley and Read [19] and later Rong et al [20].…”
Section: A Pedmr Experiments With P B -Centersmentioning
confidence: 99%
“…P b centers are trivalent Si atoms at the c-Si/SiO 2 interface. They dominate interface trapping and recombination, they are paramagnetic when uncharged [15,16] and they are strongly localized, anisotropic electronic states [17]. For the c-Si (111) surface orientation, all P b centers point into a direction perpendicular to the interface.…”
Section: A Pedmr Experiments With P B -Centersmentioning
confidence: 99%
“…14 The dangling bonds ͑usually paramagnetic͒ play a key role in the device performance. 15 Depending on the film composition, the dominant defect has a different microscopic structure, changing its type from the well known EЈ center ("SiϵO 3 ) in stoichiometric SiO 2 films to the Si-dangling bond defect ("SiϵSi 3 , in the following Si DB ) in SROX films far from the stoichiometry. 16 The study of defects in SROX films is scarce and few articles dealing with this problem can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%